Isoflurane Post-conditioning Ameliorates Cerebral Ischemia/Reperfusion Injury by Enhancing Angiogenesis Through Activating the Shh/Gli Signaling Pathway in Rats - Peng, Li; Yin, Jiangwen; Ge, Mingyue; Wang, Sheng; Xie, Liping; Li, Yan; Si, Jun-qiang; Ma, Ketao (Frontiers in Neuroscience, 2019)
Abstract Background: Stroke is the second leading cause of death worldwide. Angiogenesis facilitates the formation of microvascular networks and promotes recovery after stroke. The Shh/Gli signaling pathway is implicated in angiogenesis and cerebral ischemia-reperfusion (I/R) injury. This study aimed at investigating the influence of isoflurane (ISO) post-conditioning on brain lesions and angiogenesis after I/R injury. Methods: Adult male Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO), 1.5h occlusion and 24h reperfusion (MCAO/R). The ISO post-conditioning group (ISO group) received 1hour ISO post-conditioning when reperfusion was initiated. Neurobehavioral tests, TTC staining, HE staining, Nissl staining, TUNEL staining, immunofluorescence (IF), immunohistochemistry (IH) and Western blot were performed to assess the effect of ISO after I/R injury. Results: ISO post-conditioning resulted in lower infarct volumes and neurologic deficit scores, higher rate of neurons survival, and less damaged and apoptotic cells after cerebral I/R injury in rats. Meanwhile, ISO post-conditioning significantly increased the expression levels of vascular endothelial growth factor (VEGF) and CD34 in the ischemic penumbra, relative to that in the Sham and I/R groups. However, cyclopamine, the specific inhibitor of the Sonic hedgehog (Shh) signaling pathway, decreased the expression levels of VEGF and CD34, and counteracted the protective effects of ISO post-conditioning against I/R injury in rats. Conclusions: ISO post-conditioning enhances angiogenesis in vivo partly via the Shh/Gli signaling pathway. Thus, Shh/Gli may represent new therapeutic targets for aiding recovery from stroke.